Investing in flexibility in an integrated planning of natural gas and power systems. Issue 2 (18th May 2020) - Ameli, Hossein; Qadrdan, Meysam; Strbac, Goran; Ameli, Mohammad Taghi
Abstract : The growing interdependencies between natural gas and power systems, driven by gas‐fired generators and gas compressors supplied by electricity, necessitates detailed investigation of the interactions between these vectors, particularly in the context of growing penetration of renewable energy sources. In this research, an expansion planning model for integrated natural gas and power systems is proposed. The model investigates optimal investment in flexibility options such as battery storage, demand‐side response, and gas‐fired generators. The value of these flexibility options is quantified for gas and electricity systems in Great Britain in 2030. The results indicate that the flexibility options could play an important role in meeting the emission targets in the future. However, the investment costs of these options highly impact the future generation mix as well as the type of reinforcements in the natural gas system infrastructure. Through the deployment of the flexibility options up to £ 24 .2 billion annual cost savings in planning and operation of natural gas and power systems could be achieved, compared to the case that no flexibility option is considered.